Property - Lamb, Robert 1979- (Polity, 2021)
"How political theorists have understood, defended and critiqued private property, from Aquinas to Rawls"--
Keywords: Politik; Eigentum; Property; Right of property / History / Philosophy; Right of property / Philosophy; History